Integrating hepatitis B virus, hepatitis C virus and human immunodeficiency virus screening for migrants from endemic countries into travel-related and sexual health care in Amsterdam, the Netherlands - Generaal, Ellen; Bachour, Yara; Klijzing, Sara; Cornelissen, Akke; Toering, Roel; Hoornenborg, Elske; Op de Coul, Eline; Hamdiui, Nora; Meiberg, Annemarie; Siedenburg, Evelien; Prins, Maria (Frontiers in Public Health, 2025)
IntroductionThe Health Council of the Netherlands has recommended screening for hepatitis B virus (HBV), hepatitis C virus (HCV) and human immunodeficiency virus (HIV) for migrants born in countries endemic for these infections. We investigated the operational feasibility, test uptake and diagnostic outcomes of integrated HBV/HCV/HIV screening into routine care at the Public Health Service (PHS) of Amsterdam.MethodsIn 2022–2023, visitors born in endemic countries (≥ 18 years) were offered free HBV, HCV and HIV testing at the Travel and Vaccination Center (TVC) of the PHS. In 2021–2022, 1,172 visitors born in an endemic country for HCV (≥ 16 years) were offered free HCV testing at the Center for Sexual Health (CSH), alongside standard free HBV/HIV testing. Countries considered endemic for HBV and HCV had a prevalence of ≥2.0% or ranked among the top-10 endemic countries in the Netherlands. The screening program was considered operationally feasible if inclusion began within six months and ≥25% (TVC) or ≥50% (CSH) of eligible visitors were included within one year. Positivity rate was considered ‘low’ for prevalence < 2.0%, and ‘high’ for prevalence ≥ 2.0%.ResultsAt the TVC, 298 visitors participated in HBV (n = 264), HCV (n = 293) and/or HIV (n = 290) testing. At the CSH 1,023 visitors underwent HCV testing. Inclusion targets were met. Test uptake at the CSH was 87%; data for TVC were unavailable. At the TVC, we identified five newly diagnosed chronic HBV cases (2.0, 95%CI = 0.6–4.4%) and no new cases for HCV or HIV. At the CSH, one newly diagnosed chronic HCV case was identified (0.1, 95%CI = 0.01–0.5%).DiscussionIntegrating HBV, HCV and HIV screening into routine travel-related care and additional HCV screening into sexual health care is operationally feasible. HBV screening at the TVC showed a high yield, while HCV and HIV yields were low. Routine HBV screening should be further examined in similar settings for migrants from endemic countries, preferably alongside HCV and HIV testing.